First Record of Aedes aegypti (L.) Vector of Dengue Virus from Kathmandu, Nepal - Gautam, Ishan; Dhimal, Megh Nath; Shrestha, Shambhu Raj; Tamrakar, Anand Shova (Journal of Natural History Museum, 2009)
Aedes aegypti is the primary vector for the transmission of Dengue Fever (DF)/Dengue Haemorrhagic Fever (DHF). Entomological investigations on breeding habitats and larval prevalence of mosquitoes Aedes aegypti (L.) and Ae. albopictus (Skuse) were conducted from April to June 2009 in Kathmandu district, Nepal. Different water-filled containers were examined for the presence or absence of Aedes larvae. Larval survey techniques were used to obtain the House Index (HI), Container Index (CI) and Breteau Index (BI). The over all HI, CI and BI for Aedes aegypti were 6.25, 4.83, 9.37 and for Aedes albopictus were 6.25, 3.22 and 6.25 respectively. It was also observed that discarded tires lying outdoors were the preferred breeding habitats. No breeding was observed in other containers in April and May during this three months survey. Herewith, we report the first collection and identification of Aedes aegypti in Kathmandu during June, 2009. Indeed, this finding constitutes the first record from the capital of Nepal within the urban agglomeration of Basundhara and Gongabu-Balaju area.Therefore, DF/DHF transmission risk may occur locally if imported cases are introduced. Key Words: Aedes aegypti; Ae. albopictus; Kathmandu; First record; Dengue Fever. Journal of Natural History Museum Vol 24, 2009. Page: